1976
DOI: 10.1002/j.1879-3479.1976.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Fetal Acid—Base Balance to duration of Second Stage of Labour

Abstract: Data from 4081 vaginal deliveries (no caesarean sections) were analyzed retrospectively (IBM 730/158) with regard to duration of second and "final stage" of labour and fetal outcome (acid-base balance and apgar scores). The average duration of the two periods amounted to 22.8+/-29.6 and 9.9+/-7.8 min. Mean pH (UA) was 7.268+/-0.084 and the acidotic risk (pH less than 7.20, pH less than 7.10) 13.4 and 1.6% respectively. The distribution of the Apgar-scores after 1 min was assessed: 0-3: 1.7%, 4-6: 5.4%, 7-10: 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 24 publications
2
18
0
2
Order By: Relevance
“…The importance of taking the full acid-base status into consideration instead of only the pH has also been acknowledged (8,14) and an acidosis with a metabolic component that develops secondarily to fetal hypoxia is thought to be of greater importance than an acidosis of mainly 'respiratory' type where an accumulation of CO 2 is predominant. One common belief has been that the shorter duration of labor achieved through AML was to the benefit of the fetus (13). Since this concept was presented it has, however, also been ascribed to have other advantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of taking the full acid-base status into consideration instead of only the pH has also been acknowledged (8,14) and an acidosis with a metabolic component that develops secondarily to fetal hypoxia is thought to be of greater importance than an acidosis of mainly 'respiratory' type where an accumulation of CO 2 is predominant. One common belief has been that the shorter duration of labor achieved through AML was to the benefit of the fetus (13). Since this concept was presented it has, however, also been ascribed to have other advantages.…”
mentioning
confidence: 99%
“…The concept of 'active management of labor' (AML) was presented by O'Driscoll and Meagher at the National Maternity Hospital in Dublin in the late 1960s and the intention of this policy was originally to shorten the duration of labor for the primiparous women and, by way of this, give them a more agreeable experience of labor (9). This is probably based upon the traditional concept that a long second stage is in itself dangerous to the fetus (15) and some studies have indeed shown that a longer duration of the second stage is associated with a lower umbilical artery pH (2)(3)(4)13). One common belief has been that the shorter duration of labor achieved through AML was to the benefit of the fetus (13).…”
mentioning
confidence: 99%
“…Ces deux forces augmentent la pression intra-amniotique jusqu'à des valeurs pouvant atteindre 250 mmHg qui diminuent les perfusions placentaire et funiculaire [6,7]. En effet, le foetus est soumis pendant cette phase d'expulsion aux forces précitées mais aussi aux forces mécaniques volontaires (efforts expulsifs).…”
Section: Phase D'expulsionunclassified
“…Dans une étude rétrospective incluant 4081 femmes de toute parité et visant à analyser la relation entre la durée du second stade du travail et l'équilibre acidobasique, Roemer et al [6] ont conclu, en 1976, que ce stade ne devait pas excéder 45 minutes.…”
Section: Phase D'expulsionunclassified
“…Table 1 summarizes the duration of second stage as reported by various investigators. The duration of the true length of second stage is of considerable clinical interest because fetal acidosis has been shown to become more pronounced the longer the time between complete dilatation and delivery 96–98,100–103 …”
Section: Duration Of the Second Stage In Vertex Presentationmentioning
confidence: 99%